Perancangan Line Produksi Perusahaan Manufaktur Otomotif Melalui Implementasi 5S dalam Upaya Peningkatan Kapasitas Produksi Menggunakan Metode Eight Steps - Haryo Sutedi; Constantius Chrisnaputra; Rifdah Zahabiyah (Universitas Teuku Umar, 2026)
Automotive Manufacturing Industries is an American-based manufacturing company specializing in the production of automation instruments that support scientific research in proteomics and genomics. The company faces a production challenge in increasing the Manufacture Company line output from two to three units per month to meet the target set by Manufacturing Corp. USA. The primary issue identified is the lack of standardized work processes, particularly in the arrangement of tools and components, which leads to inefficiency and reduced productivity. This study aims to establish standardized work procedures to enhance operational efficiency and production capacity. The research adopts the Eight Steps methodology integrated with the 5S approach (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). The improvement initiatives include reorganizing tools and components using toolboxes and trolleys, implementing labeling systems, and developing Standard Operating Procedures (SOPs). The results demonstrate a substantial improvement in production performance, with assembly time per unit reduced from 106 hours to 61 hours, representing a 57% reduction. Additionally, an operator satisfaction survey indicates a 94% success rate of the implemented improvements. The findings confirm that the application of the 5S method effectively enhances production capacity, achieves target performance, and resolves operational inefficiencies.